Development of Teaching Materials for Writing Short Stories With Expressive Writing Methods - Astriyanti Astriyanti; Ramly Ramly; Sultan Sultan (HUMAN: South Asian Journal of Social Studies, 2021)
Abstract. This study aims to: (1) Produce a structure of short story writing teaching materials using the expressive writing method for seventh grade students of SMP IT Al-Hikmah Maros; and (2) examining the results of the validity of the structure of short story writing teaching materials using the expressive writing method for seventh grade students of SMP IT Al-Hikmah Maros. This research uses the type of research and development Research and Development (R & D) with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model which is used in developing Instructional Design. The data used, firstly qualitative data, is data obtained from the results of interviews, questionnaires, suggestions, criticism from Indonesian language teachers and students as well as expert opinions. Second, quantitative data is a type of data obtained from the results of the validation test using a formulation that produces an assessment score from the validator of the teaching materials developed. The module has been tested for validation by experts and practitioners, there are four aspects tested for validation, namely: (1) content / material aspects with an average value of 0.92 (very feasible), (2) presentation aspects with an average value of 0.91 (very feasible), (3) language feasibility with an average value of 0.90 (very feasible), (4) graphic feasibility with an average value of 0.92 (very feasible). Based on the results of each aspect, it shows that the teaching material module developed is very suitable to be used as a teaching material module. Keywords: teaching materials module, short story writing, expressive writing, students